Making British Law - Thompson, Louise. author. aut Link
XIII, 142 p.
Keywords: Laws are essential to the lives of all British citizens and crucial to the survival of British Governments. This book follows the work of House of Commons bill committees as they scrutinise legislation and reveals the hidden depths of law making in the British Parliament.